PHYSIOLOGICAL AND PATHOLOGICAL CHANGES OF THE CARDIOVASCULAR SYSTEM AND THEIR CLINICAL SIGNIFICANCE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The cardiovascular system plays a fundamental role in maintaining human life by ensuring the continuous circulation of blood, oxygen, nutrients, and metabolic products throughout the body. This article explores the physiological and pathological changes of the cardiovascular system and their clinical significance. It highlights the mechanisms of normal cardiac function, vascular regulation, and hemodynamic balance, as well as the alterations that occur in various cardiovascular diseases such as hypertension, atherosclerosis, heart failure, and ischemic heart disease.